PENGARUH LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA KARYAWAN PADA PT. PUPUK SRIWIDJAJA PALEMBANG, PUSRI PEMASARAN DAERAH (PPD) JAWA TENGAH - Heni Ingsiyah; Putut Haribowo; Isnaini Nurkhayati (Politeknik Negeri Semarang, 2019)
The purposes of this research were to find out (1) The influence of physical work environment on employees’ work motivation at PT. Pusri Palembang, PPD Jateng, (2) The influence of non-physical work environment on employees’ work motivation at PT. Pusri Palembang, PPD Jateng, and (3) work environment on employees work motivation at PT. Pusri Palembang, PPD Jateng. This study was a survey method with questionnaires, and literature study. The sample in this study were 35 employees’ of the PT. Pusri Palembang, PPD Jateng. The data analysis technique used was multiple regression. From the analysis of multiple regression in this research, it could be found that the physical work environment and non-physical work environment had positive impact on the employees’ work motivation. The most dominant variable that positively influenced the employees’ work motivation was the non physical work environment. While from the result of determination coefficient (Adjusted R Square) showed that 0,46 or 46% of the independent variable were physical work environment and non-physical work environment. It meant that 46% of the employees’ work motivation was explained by work environment. While 54% was explained by other factors not examined in this research.